Les vedettes du Dictionnaire Électronique des Synonymes et les relations d’adjacence entre leurs synonymes - Laurette Chardon; Jacques François (Lexique, 2020)
The Dictionnaire Électronique des Synonymes of CRISCO (DES, Université de Caen-Normandie) has acquired an undisputed reputation over the last twenty years. The synonymic links that originally originated from 7 source dictionaries have been progressively completed by tens of thousands of proposals from Internet users, whose relevance has been tested and validated by the successive engineers and webmasters of the DES. The present study deals with the utilization of the adjacency graph between all registered synonyms, their distribution into two or more sets of interconnected synonyms, and especially the question of the numerous isolated synonymic links whose integration into an interrelated component is being tested using an original method of exploiting second-order synonymic links. This method, which delivers a high integration rate (between 70% and 80%, irreducible links being removed), will allow an appreciable cleaning of the synonymic network of the DES.